Central Europe and NATO Transformation 2014–2018 - Gizicki, Wojciech (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2019)
The collapse of the Cold-War order in Europe brought about a radical change in the global security system. The dissolution of the Soviet Union and the disbandment of the Warsaw Pact created a situation where the only serious and effective guarantee of stability in Europe was NATO. Central European states, which until that time had been subordinated to the USSR, un- equivocally and consistently chose to pursue the Euro-Atlantic direction in their security policy. The decision resulted in their gaining full, even though gradual, membership in the Alliance during the years 1999–2004. The accession process was first completed by the Czech Republic, Hungary and Poland. Central Europe is not free from dangers stemming from national and su- pranational transformations. NATO is facing the need to increase its activity and systematically ensure joint cooperation and security guarantees as regards all its member states. This is pri- marily caused by a revival of Russia’s superpower ambitions under the presidency of Vladimir Putin and an escalation of terrorism and cyberspace threats. The decisions and practical actions related to biennial NATO summits are of vital importance in this respect. The text presented here is an analysis of the security of Central Europe within NATO structures in the light of the last three NATO summits: in Newport in 2014, in Warsaw in 2016 and in Brussels in 2018.

Upadek porządku zimnowojennego w Europie spowodował radykalną zmianę w globalnym systemie bezpieczeństwa. Rozpad Związku Radzieckiego i likwidacja Układu Warszawskiego doprowadziły do sytuacji, w której jedynym poważnym i efektywnym gwarantem stabilności Europy stało się NATO. Państwa Europy Środkowej, które dotąd podporządkowane były ZSRR jednoznacznie i konsekwentnie wybrały euroatlantycki kierunek w polityce bezpieczeństwa. Efektem tego stało się ich pełne, choć stopniowe członkostwo w Sojuszu w latach 1999–2004. Pionierami w tym względzie były Czechy, Węgry i Polska. Europa Środkowa nie jest wolna od zagrożeń związanych z przemianami na poziomie narodowym lub ponadnarodowym. Odrodzenie się mocarstwowych ambicji w Rosji rządzonej przez Władimira Putnia, eskalacja zagrożeń terrorystycznych bądź zagrożenia w cyberprzestrzeni wymagają od NATO większej aktywności i systematycznego potwierdzania solidarnej współpracy i gwarancji bezpieczeństwa wobec wszystkich członków. Kluczowe znaczenie w tym względzie mają decyzje i praktyczne działania związane z cyklicznymi Szczytami NATO. Prezentowany tekst podejmuje analizę bezpieczeństwa Europy Środkowej w ramach NATO w świetle trzech ostatnich szczytów: 2014 w Newport, 2016 w Warszawie i 2018 w Brukseli.
Europa Środkowa w ramach transformacji NATO 2014-2018
Keywords: NATO; NATO Summit; Central Europe; transatlantic security; NATO; szczyt NATO; Europa Środkowa; bezpieczeństwo euroatlantyckie